REKONSTRUKSI KEPERCAYAAN PUBLIK TERHADAP MBG DALAM MENDUKUNG TUMBUH KEMBANG DAN KUALITAS PEMBELAJARAN ANAK: PERSPEKTIF EKONOMI SYARIAH - Muhammad Adam (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The Free Nutritious Meal Program (MBG) is a national strategic policy aimed at reducing stunting and improving human resource quality towards a Golden Indonesia. However, its implementation has triggered polarization and a crisis of public trust related to fiscal sustainability, the risk of corruption, and the marginalization of the local real sector. This study aims to reconstruct this public trust through the lens of Islamic Economics. The method used is descriptive qualitative with a literature study approach and analysis of Maqashid Syariah. The results show that reconstructing public trust can be achieved through four main pillars: (1) Transparency in governance based on the principle of Amanah and optimization of the function of modern Hisbah; (2) Equitable distribution (Al-'Adl) by integrating MSMEs and local farmers through the Syirkah contract; (3) Certainty of the Halal Thayyiban supply chain; and (4) Diversification of funding using prudent Islamic Social Finance. This integration of sharia values ​​shifts the MBG paradigm from a mere populist program to a sustainable instrument for public welfare.